Influence of densities on the growth of brown mussel Perna perna L. cultivated in suspended socks at Caraguatatuba, southeastern Brazil - Bordon, Isabella C.A.C.; Marques, Helcio L.A.; Alves, José L.; Rossi, André [UNESP]; Pecora, Iracy Lea [UNESP] (Springer Nature, 2013)
This study was carried out in a marine area at Cocanha Beach, Caraguatatuba, southeastern Brazil, aiming to determine the most appropriated density for brown mussel (Perna perna L.) cultured in suspended socks (French System), in order to reduce costs with acquisition of juvenile mussels (seed) and labor. In September 2007, 15 socks measuring 2 m each were reared at densities of 300, 400 and 500 seeds/m. After 250 days, mussels were harvested and separated in two length classes: non-commercial (<6 cm) and commercial (≥6 cm). Mussels were counted and weighed. In August 2008, the experiment was repeated with 1-m-long socks at lower densities (200, 250 and 300 seeds/m) in order to identify differences among commercial-sized mussels only. Data were analyzed by ANOVA or nonparametric Kruskal-Wallis test, followed by Tukey or SNK tests, respectively. The results suggest that it is feasible to use densities from 250 to 300 seeds/m, since biomass yields are similar to those registered at higher densities and the use of mussel seed is therefore optimized. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Aquaculture; Brazil; Mussel farming; Perna perna; Seed